The importance of species selection and seed sourcing in forest restoration for enhancing adaptive potential to climate change: Colombian tropical dry forest as a model - Thomas, E.; Alcázar, C.; Moscoso Higuita, L.G.; Osorio, L.F.; Salgado Negret, B.; González, M.; Parra, M.; Bozzano, M.; Loo, J.; Jalonen, R.; Ramírez, W. (Secretariat of the Convention on Biological Diversity, 2017)
• Forest restoration projects can derive great benefit from integrating climate modeling, functional trait analysis and genetic considerations in the selection of appropriate tree species and sources of forest reproductive material, for their critical importance for the delivery of ecosystem services and the viability and adaptive capacity of restored forests. • Targets in restoration projects are not only quantitative but also qualitative. There is need for political commitment to create demand for good quality forest reproductive material of native species through regulatory frameworks and resource allocations. • User friendly knowledge-based decision making tools need to be developed and mainstreamed to assist emerging restoration practitioners with the choice of tree species and sources of forest reproductive material. • Countries need to increase experimental field setups such as provenance and progeny trials for native species to validate decision tools and apply adaptive management under climate change. • Seed supply systems for restoration need to be diversified by involving and training stakeholders at different levels of society.